Pengembangan Lembar Kerja Siswa Berbasis STAD Pada Materi Sistem Persamaan Linier Dua Variabel di SMP - Asri Putri Anugraini; Brian Gilbert Eleuwarin (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
This research aims to develop student worksheets that can improve the quality of student learning, using the STAD learning model, and creating a fun learning process. This research began with interviews with school teachers discussing the use of learning media, the learning methods used in class, and the situation with students learning mathematics. In this school, it was found that there were worksheets that were less attractive to students, so the researchers came up with the idea of ​​developing interesting two-variable linear worksheets based on STAD. The worksheet that has been developed is validated by expert speakers and media experts to determine the validity of the content of the student worksheet so that it is suitable for research use. The results of the development of the student worksheet Linear Equations for Two Variables when tested, students obtained results from the analysis of effective criteria from aspects of student activity, student responses, and student learning outcomes, with an average score of 4.06, the student worksheet was declared in the category Very Effective. and when students work on STAD-based student worksheets, the results are above the maximum completeness criteria, reaching an average of 86.